RETRACTED ARTICLE: Prioritizing customer and technical requirements for microgrid battery integration via a house of quality-driven decision-making approach - Hasan Dinçer; Serhat Yüksel; Serkan Eti; Yaşar Gökalp; Alexey Mikhaylov; Jaehyung An (Scientific Reports)
Abstract The purpose of this study is to make evaluation regarding significant issues about the customer expectations and technical competencies for successfully integration of batteries in microgrid systems. In this direction, six different customer expectations and technical requirements are identified by considering literature review results. The weights of the criteria are computed with sine trigonometric Pythagorean fuzzy (STPYF) decision making trial and evaluation laboratory (DEMATEL). Moreover, technical requirements are also ranked using a newly developed technique in this study called “ranking technique by geometric mean of similarity ratio to optimal solution” (RATGOS). This new methodology is also integrated with STPYF sets. The main contribution of this study is that it can be much easier to increase the efficiency of battery integration in microgrid systems by making the priority analysis. Moreover, proposing a new ranking-based decision-making technique (RATGOS) has an increasing impact on the methodological originality. On the other side, owing to considering DEMATEL approach in criteria weighting, the causal directions between these factors can be understood. This situation can be accepted as an important superiority of this model by comparing with the previously generated ones. It is determined that efficiency of storing energy is the most critical customer expectation to increase the effectiveness of this process. Furthermore, the ranking results also demonstrate that generating smart battery control systems is the most important technical requirements to have higher performance in microgrid energy systems. It is identified that the proposed model generates similar findings with the previous ones. Based on these results, some strategies should be implemented to increase the efficiency of energy storage processes in microgrid systems. Within this framework, choosing the right battery is of vital importance. Technological infrastructure is necessary to achieve this goal. Similarly, it is important to provide cyber security to increase the efficiency of energy storage processes. In this way, it is possible for the batteries to work more safely against external interventions.